Critical review of latent heat storage systems for free cooling in buildings - Zeinelabdein, Rami; Omer, Siddig; Gan, Guohui (Elsevier, 2018)
Buildings have a major contribution to the global energy consumption. Heating, ventilating and air conditioning systems (HVAC) are responsible for most of the energy use in buildings. Thus, clean and sustainable alternatives such as free cooling of buildings have recently gained much attention as means to reduce the operation hours and capacity of the conventional cooling and heating systems. The free cooling could be provided by collecting the natural cold energy during night time in appropriate thermal storage form and this could be retrieved when needed. Phase change materials are exploited by a number of investigators as a storage medium in free cooling applications, as these substances possess high energy densities, and absorb and release heat at a narrow temperature range, hence, the comfort temperature can be maintained day and night. The objectives of this article are to provide a comprehensive review on recent development on free cooling technologies incorporating latent heat storage and to shit lights on the most significant parameters affecting the performance of these materials in free cooling strategy. The outcomes of this review would be helpful in providing clear insight information on potential improvements that can be applied to the storage materials. All the reviewed studies demonstrated that the night cooling strategy using PCMs has the capacity to maintain the indoor temperature well within the comfort zone whilst providing a considerable reduction in cooling loads in all considered climates.